THE EFFECT OF NATURAL PRESERVATIVE EXTRACTS ON THE PHYSICOCHEMICAL AND ANTIOXIDANT ACTIVITY OF COCONUT SAP - Desi Riana Saputri; Yuniar Luthfia Listyadevi; Galeh Widharma; Ratih Ainun Mardiyah; Muhammad Triyogo Adiwibowo; Wika Atro Auriyani; Yunita Fahni; Damayanti Damayanti; Andri Sanjaya; Feerzet Achmad; Deviany Deviany; Aldillah Herlambang; Edwin Rizki Safitra (JURNAL INTEGRASI PROSES, 2024)
Coconut sap produced from coconut trees has a short shelf life due to contamination and undergoes natural fermentation. One way to extend the shelf life of coconut sap is by adding preservatives. This research aims to determine the effect of adding natural preservative extracts on the antioxidant value, pH, sugar, and alcohol content of coconut sap by adding natural preservatives. There are five samples: pure sap (NM); sap with sugar lime (NK); sap with sugar lime and cinnamon extract (NKM); sap with sugar lime and mango leaf extract (NDM); sap with sugar lime and noni leaf extract (NKD). The study was conducted by extracting natural preservatives, namely cinnamon extract, mango leaves extract, and noni leaves extract, using the maceration method. These natural preservative extracts were mixed with Ca(OH)2 in a 1:1 ratio and dissolved in distilled water. The mixture was then mixed with the sap. The results of the antioxidant test showed that the IC50 values of the NM, NK, NKM, NDM, and NKD samples were 52.911, 144.409, 26.043, 49.275, and 24.21 ppm, respectively. The highest pH value was found in the NK sample at 13.8, and the lowest in the NM sample at 3.8. The lowest sugar content was in the NM and NDK samples, with 10.6 and 14.6%. The highest alcohol content was found in the NK and NKD samples, with alcohol contents of 14.80% and 14.20%. This study shows that adding natural preservatives such as cinnamon, mango leaves, and noni leaves can increase the antioxidant activity of coconut sap, raise its pH, and maintain its sugar content to prevent it from being reduced to alcohol.